Ethical foundations of competitive order according to Walter Eucken - Kamińska, Katarzyna (Annales. Etyka w Życiu Gospodarczym, 2019)
Ordoliberalism is a German economic and legal doctrine, in which ethics occupies a privileged place. The basic premise is the freedom and responsibility of human beings. In contrast, the starting point for considering ordoliberalism as a doctrine is the economic, social and political order. The most prominent representative of ordoliberalism was Walter Eucken. Achievements of this outstanding economist as well as other representatives of this school underlay the concept of the German social market economy and the EU competition policy. The aim of this article is to present the concept of Eucken’s competitive order and describe its philosophical and ethical foundation. The article relies on descriptive analysis and literature studies.